List of referees for the year 2023 - Gaćeša, Nebojša (Vojnotehnički glasnik / Military Technical Courier, 2023)
All submitted manuscripts relevant to the journal’s profile are reviewed. All referees are eminent external experts in relevant fields, with papers published in these fields in the last three years. The reviewers must not be from the authors' own institution and they should not have recent joint publications with any of the authors. Editorial Board applies the iThenticate (CrossRef and CrossCheck) service for verifying the originality of submitted papers and for preventing duplicate publishing and plagiarism. Journal applies a „double blind peer review process“ for papers. Authors and reviewers are anonymous to each other in the process of review. Reviews after the article has been published are allowed and encouraged for subsequent evaluation of papers and authors.